2018
DOI: 10.1159/000487327
|View full text |Cite
|
Sign up to set email alerts
|

Weight Status of 7-Year-Old Hungarian Children between 2010 and 2016 Using Different Classifications (COSI Hungary)

Abstract: Aims: To describe the prevalence of thinness, overweight, and obesity in Hungarian children (age 7.0-7.9 years) according to different classifications, to assess the progress between 2010 and 2016, and to investigate whether tendencies differ according to gender. Methods: A national representative sample was generated by two-stage cluster sampling, and a total of 2,651 children (50.9% boys; age 7.49 ± 0.3 years) were measured (weight and height) in October 2016. Population estimates were calculated using the W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
7
1
5

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 22 publications
1
7
1
5
Order By: Relevance
“…Previous data from this region showed that the frequency of overweight and obese children in Hungary increased from the 1980s to the first decade of the 2000s [36]. However, according to more recent data, a stable childhood obesity rate is observed after 2010 in the country [37]. As no data are available on the obesity rate in the current study, it can be speculated that this could contribute to the decreasing tendency of T2DM in childhood.…”
Section: Discussioncontrasting
confidence: 63%
“…Previous data from this region showed that the frequency of overweight and obese children in Hungary increased from the 1980s to the first decade of the 2000s [36]. However, according to more recent data, a stable childhood obesity rate is observed after 2010 in the country [37]. As no data are available on the obesity rate in the current study, it can be speculated that this could contribute to the decreasing tendency of T2DM in childhood.…”
Section: Discussioncontrasting
confidence: 63%
“…These differences may be due to the age groups under study. Seven-year-olds in Hungary and 8–9-year-olds in Italy demonstrated stabilizing levels of overweight and obesity [ 28 ]. While other researchers have reported similar findings in preschool and primary school-aged children, these trends did not hold in older children or adolescents [ 23 , 24 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Overweight or general obesity is more common in boys than in girls [ 21 ]. An inverse relationship among 7-year-olds was observed in Hungary [ 22 ]. The prevalence of overweight and obesity in Hungarian children (aged 7.0–7.9 years) according to various classifications in 2010–2016 indicated the possible stability of the prevalence of overweight and obesity [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…An inverse relationship among 7-year-olds was observed in Hungary [ 22 ]. The prevalence of overweight and obesity in Hungarian children (aged 7.0–7.9 years) according to various classifications in 2010–2016 indicated the possible stability of the prevalence of overweight and obesity [ 22 ]. Our results indicated an unfavorable increase in the incidence of overweight and obesity with age in boys.…”
Section: Discussionmentioning
confidence: 99%